Sexual Dysfunctions in Men and Women with Inflammatory Bowel Disease: The Influence of IBD-Related Clinical Factors and Depression on Sexual Function. (1st July 2015) - Bel, Linda G.J.; Vollebregt, Anna M.; Van der Meulen‐de Jong, Andrea E.; Fidder, Herma H.; Ten Hove, Willem R.; Vliet‐Vlieland, Cornelia W.; ter Kuile, Moniek M.; de Groot, Helena E.; Both, Stephanie
ABSTRACT: Introduction: Inflammatory bowel disease (IBD) is likely to have an impact on sexual function because of its symptoms, like diarrhea, fatigue, and abdominal pain. Depression is commonly reported in IBD and is also related to impaired sexual function. This study aimed to evaluate sexual function and its association with depression among patients with IBD compared with controls. Methods: IBD patients registered at two hospitals participated. The control group consisted of a general practitioner practice population. The web‐based questionnaire included the Female Sexual Function Index (FSFI) for women and the International Index of Erectile Function (IIEF) for men. Other variables evaluated were depression, disease activity, IBD‐related quality of life, body image, and fatigue. Results: In total, 168 female and 119 male patients were available for analysis (response rate 24%). Overall, patients with IBD did not significantly differ in prevalence of sexual dysfunctions from controls: female patients 52%, female controls 44%, male patients and male controls both 25%. However, men and women with an active disease scored significantly lower than patients in remission and controls, indicating impaired sexual functioning during disease activity. Significant associations were found between active disease, fatigue, depressive mood, quality of life, and sexual function for both male and female patients. The association between disease activity and sexual function was totally mediated by depression. Conclusion: Male and female IBD patients with an active disease show impaired sexual function relative to patients in remission and controls. Depression is the most important determinant for impaired sexual function in IBD.